Population dynamics of Melanorivulus rossoi, a restricted geographic distribution killifish species - Severo-Neto, Francisco [UNESP]; Volcan, Matheus Vieira (Springer Nature, 2018)
Species of Melanorivulus present behaviour and physiological traits that allow them to live in marginal aquatic habitats. In particular, Melanorivulus rossoi is a small nonannual fish only known from its type locality in the Brazilian Cerrado. In this study, we aimed to characterize the distribution and temporal variation in body size, sex ratio, density, length-weight relationship (LWR) and condition factor (CF) of M. rossoi in its natural habitat. To accomplish this, fish samples were taken monthly for a year using sieve nets every 30 min. Body size of males and females increased throughout the year until early summer. LWR was significant, and general coefficient of determination (r2) was 92%. Juveniles showed negative allometric growth, but adults showed positive allometric growth. Both sexes presented the same tendency of temporal variation in CF, with lower values in October and January and peaks in September and February. Fire occurred in June, but no difference in population parameters was observed after this event. A decrease in the abundance of Melanorivulus was related with an increase in the abundance of Erythrinidae juveniles. This might be explained by an increased predation of this species over the M. rossoi individuals, when the population was reduced to about 30% of that in the previous months. We report four new locations where this species was recorded; thus, similar to most Rivulidae members, M. rossoi has a restricted distribution area and is threatened with extinction. Therefore, our results may be useful in developing management strategies aimed at conservation of this species and its habitat in Brazil.
Keywords: Cerrado; Melanorivulus; Rivulidae; Threatened species; Wetlands